Television studies - Gray, Jonathan; Lotz, Amanda D. 1974- (Cambridge, United Kingdom Polity, 2019)
"Television Studies provides an overview of the origins, central ideas, and intellectual traditions of television studies. For all those wondering how to study television, or even why to study television, this new edition will provide a clear and engaging overview of key topics"-- Provided by publisher.
Introduction: still television studies? -- Programs -- Audiences -- Industries -- Contexts.
Includes bibliographical references (pages [145]-179) and index.
Keywords: Television broadcasting -- History and criticism -- History